Dose response of Maple Pea (Pisum sativum L.) microgreens to biochar as a priming agent with optimal growth medium - Chin, Nicole Jiaxuan (Nanyang Technological University, 2023)
Biochar is commonly used as an amendment to soil due to its influence on physical and chemical properties of the soil. Despite wide biochar utilization for soil improvement, only few scientific reports have utilized biochar extract to grow microgreens, with even fewer scientific reports using biochar extract for seed quality improvement through seed priming. The present report investigates the benefits of biochar extract as a seed priming solution, with extracts from 1% and 3% (wt%) biochar mixtures being used as the priming solution. In addition, the report investigates the optimal growing substrate for improvement of microgreen yield and growth. Studies were undertaken to evaluate the use of extracts from biochar (1% and 3%, wt%) water mixtures, and 3 growing matrices (deionised water (DI water), peat moss, and soil) in a factorial arrangement to enhance seed quality. It was observed that the choice of growing substrate was the major determinant in microgreen yield and growth. Parameters such as chlorophyll content, average root and shoot length, fresh and dry weights, and the nutritional profile proved that peat moss was the best growth substrate, followed by soil, and lastly DI water. The effect of biochar extract as a priming solution was only observed in the average root and shoot length, with the 3% biochar (BC) extract producing microgreens with the highest growth, followed by DI water and lastly, 1% biochar (BC).